The extended time evolution size decrease of gold nanoparticles formed by the Turkevich method - Uppal,MA; Kafizas,A; Lim,TH; Parkin,IP (New Journal of Chemistry, 2010)
Gold nanoparticle (Au NP) solutions were synthesised by the Turkevich reduction method and stored in either the light or dark. All solutions were monitored daily using UV-visible absorption spectroscopy and displayed surface plasmon resonance (SPR), typical of Au nanoparticle colloids. An increase in SPR intensity, a narrowing of the SPR peak as well as a gradual shift towards lower wavenumbers over time indicated a decrease in average nanoparticle diameter and a more mono-dispersed particle size. After two weeks no further changes were observable by UV-visible absorption spectroscopy. A series of high resolution transmission electron micrographs (HRTEM) taken over the evolution period confirmed that the plasmon resonance shifts correlated to a decrease in nanoparticle size. A systematic size decrease in nanoparticle size was also observed for solutions even after centrifugation to remove the excess un-reacted citrate and auric acid. This indicated that the size evolution was independent of further excess reactant chemistries and charge stabilities. The gold nanoparticle evolution followed an inverse Ostwald type growth, by which the size of the NPs decreases, in effect a digestive ripening. The aging process provides a reliable route to fairly mono-dispersed gold nanoparticles of ca. 11.5–12.5 nm in size via the Turkevich method.